PP2A-Like Protein Phosphatase (Sit4) Regulatory Subunits, Sap155 and Sap190, Regulate Candida albicans’ Cell Growth, Morphogenesis, and Virulence - Han, Qi; Pan, Chaoying; Wang, Yueqing; Zhao, Linpeng; Wang, Yue; Sang, Jianli (Frontiers in Microbiology, 2019)
PP2A-like phosphatases share high homology with PP2A enzymes and are composed of a catalytic subunit and a regulatory subunit. In Candida albicans, the PP2A-like catalytic subunit SIT4 regulates cell growth, morphogenesis, and virulence. However, the functions of its regulatory subunits remain unclear. Here, by homology analysis and co-IP experiments, we identified two regulatory subunits of SIT4 in C. albicans, SAP155 (orf19.642) and SAP190 (orf19.5160). We constructed sit4Δ/Δ, sap155Δ/Δ, sap190Δ/Δ, and sap155Δ/Δ sap190Δ/Δ mutants and found that deleting SAP155 had no apparent phenotypic consequence, while deleting SAP190 caused slow growth, hypersensitivity to cell wall stress, abnormal morphogenesis in response to serum or genotoxic stress (HU and MMS), less damage to macrophages, and attenuated virulence in mice. However, deleting both SAP155 and SAP190 caused significantly stronger defects, which was similar to deleting SIT4. Together, our results suggest that SAP190 is required for the function of SIT4 and that SAP155 can partially compensate for the loss of SAP190 in C. albicans. Given the vital role of these regulatory subunits of SIT4 in C. albicans physiology and virulence, they could serve as potential antifungal targets.